2020
DOI: 10.1111/clr.13564
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous progression of experimental peri‐implantitis in augmented and pristine bone: A pre‐clinical in vivo study

Abstract: Objective To examine the progression of experimental peri‐implantitis around different implants placed in augmented and pristine sites. Materials and Methods Six labrador dogs were used. Three months after tooth extraction, four implants with different surface modifications were installed on each side of the mandible. A standard osteotomy was applied on one side, while on the contralateral side the osteotomy was modified, resulting in a gap between the implant and the bone wall. The gap was filled with a bone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 32 publications
2
27
0
Order By: Relevance
“…Into the bargain, clinical 37 and preclinical 38 data pointed out that peri‐implantitis resolution in implants with turned surface was more efficient than with micro‐rough surfaces. Notwithstanding, to our best knowledge, this is the first experimental report testing the concept of hybrid implants compared to previous trials that evaluated machined‐surface implants 1,30,31,39 . Our findings indicated that implant surface characteristics in the coronal aspect of the influences the pro‐inflammatory profile (IL‐1β) during spontaneous progression of peri‐implantitis.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Into the bargain, clinical 37 and preclinical 38 data pointed out that peri‐implantitis resolution in implants with turned surface was more efficient than with micro‐rough surfaces. Notwithstanding, to our best knowledge, this is the first experimental report testing the concept of hybrid implants compared to previous trials that evaluated machined‐surface implants 1,30,31,39 . Our findings indicated that implant surface characteristics in the coronal aspect of the influences the pro‐inflammatory profile (IL‐1β) during spontaneous progression of peri‐implantitis.…”
Section: Discussionmentioning
confidence: 62%
“…Notwithstanding, to our best knowledge, this is the first experimental report testing the concept of hybrid implants compared to previous trials that evaluated machined-surface implants. 1,30,31,39 Our findings indicated that implant surface characteristics in the coronal aspect of the influences the pro-inflammatory profile (IL-1β) during spontaneous progression of peri-implantitis. From these data, it can be speculated that in individuals prone to develop peri-implantitis based on altered susceptibility (ie, with history of periodontal disease, irregular supportive care or suboptimal plaque control), 40…”
Section: Future Directionsmentioning
confidence: 61%
“…All oral hygiene measures were abandoned, and plaque formation was allowed until the end of the experiment. The ligatures were removed 4 weeks later (Carcuac et al, 2020). The radiographic examination was repeated at 3, 6 and 8 months after abutment connection, and the microbiological sampling was repeated at 6 and 7.5 months after abutment connection.…”
Section: Checkerboard Dna-dna Hybridization Techniquementioning
confidence: 99%
“…For instance, the prevalence of peri-implantitis in patients with implants in augmented sites is more variable and less predictable compared with the prevalence in patients with implants in pristine sites [40][41][42][43][44]. There are differences in bone loss during the spontaneous progression period between pristine and augmented: the size and vertical dimension of the peri-implantitis lesion were larger at augmented than at pristine sites and the findings seemed to be confirmed by clinical data, which showed a faster and worsening progression of peri-implantitis in augmented bone [45].…”
Section: Overdentures (Ovd)mentioning
confidence: 99%